The ketolide antibiotic HMR 3647, a candidate substance for the treatment of systemic and intracerebral infections with Listeria monocytogenes - Nichterlein, Thomas; Kretschmar, Marianne; Hof, Herbert (Zentralblatt für Bakteriologie, 1999)
HMR 3647 is a novel macrolide derivative with a broad spectrum of activity against grampositive bacteria and some fastiduous gramnegative bacteria, anaerobes and Toxoplasma gondii. In this work, its activity against the facultatively intracellular bacterium, Listeria monocytogenes, was examined in vitro, in tissue culture and in animal models of systemic and intracerebral infection and compared with that of erythromycin. All strains of L. monocytogenes were susceptible to the substance, with minimal inhibitory concentrations (MICs) that were consistently lower than the MICs of erythromycin. HMR 3647 was bacteriostatic against L. monocytogenes since concentrations of up to 64 times the MIC did not kill the bacteria within 24 hours. HMR 3647 produced a pronounced postantibiotic effect (PAE) and was bacteriostatic in tissue culture cells infected with L. monocytogenes. In animal models of systemic and intracerebral infection, HMR 3647 was slightly more effective than erythromycin in the livers and spleens and comparably effective in the brains when given in the same dosage. In conclusion, HMR 3647 is a candidate substance for the treatment of infections with L. monocytogenes in immunocompetent subjects.